2014
DOI: 10.1097/phm.0000000000000123
|View full text |Cite
|
Sign up to set email alerts
|

Disability Predictors in Chronic Low Back Pain After Aquatic Exercise

Abstract: The physical and psychological factors associated with reduction of disability after aquatic exercise are not well understood. Sixty participants (30 men and 30 women; age, 50.60 [9.69] yrs; body mass index, 27.21 [5.20] kg/m²) with chronic low back pain were prospectively recruited. The 8-wk aquatic therapy program was carried out in an indoor pool sized 25 × 6 m, with 140-cm water depth and 30°C (1°C) of water temperature, where patients exercised for 2-5 days a week. Each aquatic exercise session lasted 55-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
0
9
0
5
Order By: Relevance
“…The FOTO group's mean NRS was 7.8 and the IBI group's NRS was 7.5, classifying all group participants with severe pain. 33 The majority of exercise intervention studies for NSCLBP that we reviewed reported mean baseline NRS scores ranging between 3.1 and 6.4 [40][41][42][43][44][45] with a pain classification of mild to moderate, 33 or 1-2 classifications below participants in our study. A change of -2 points has been found to be associated with clinically important outcomes such as reduction in pain medication intake or returning to work or both.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The FOTO group's mean NRS was 7.8 and the IBI group's NRS was 7.5, classifying all group participants with severe pain. 33 The majority of exercise intervention studies for NSCLBP that we reviewed reported mean baseline NRS scores ranging between 3.1 and 6.4 [40][41][42][43][44][45] with a pain classification of mild to moderate, 33 or 1-2 classifications below participants in our study. A change of -2 points has been found to be associated with clinically important outcomes such as reduction in pain medication intake or returning to work or both.…”
Section: Discussionmentioning
confidence: 81%
“…Additionally, our participants' baselines ODI scores were 41.9 and 46.8 for the FOTO and IBI groups, respectively, classifying our participants regardless of group as having severe disability, 38,39 whereas the majority of exercise intervention studies for NSCLBP that we reviewed reported mean baseline ODI scores of 19.44-39, [40][41][42][43][44][45][47][48][49][50][51] classifying these participants as having minimal to moderate disability. 38,39 The NRS pain and ODI disability scores are among the outcome measures most commonly used by physical therapists.…”
Section: Discussionmentioning
confidence: 97%
“…Among the variables that other exercise studies have evaluated for predicting response are participant age, sex, and disability, and the type or dosage of interventions. [4][5][6] Improvements in body awareness might also be highly relevant to chronic neck and back pain, because studies have repeatedly pointed at the link between those pain conditions and disturbed body image, especially in chronic back [7][8][9] and neck pain. 10,11 A variety of body image measures have been used in research before including measures of proprioception and kinesthetic sense, [12][13][14][15][16] of interoceptive awareness, 17,18 and of postural awareness.…”
mentioning
confidence: 99%
“…De acordo com Baena-Beato et al 11 , a relação entre incapacidade e dor é bidirecional e um processo complexo, pois a incapacidade é um sintoma de dor que resulta em perda de função. Em seu estudo, ficou concluído que alterações na intensidade da dor e na musculatura abdominal foram preditores significativos de mudança na incapacidade em pacientes com dor lombar crônica; os pacientes com dor lombar crônica que se sentem mais incapacitados são aqueles menos ativos fisicamente.…”
Section: Discussionunclassified